Examining the Mediating Role of Customer Trust in the Relationship Between Gold Savings and Investment Interest at Pegadaian Syariah - Mutmainah Mutmainah; Mahmud Mahmud; Lilis Marlina (Advances in Management & Financial Reporting, 2026)
Purpose: This study evaluates the effect of the Gold Savings Program on investment interest by examining the mediating role of customer trust. Research Method: Using an explanatory quantitative approach, data were collected from 96 customers at PT Pegadaian Syariah’s Dompu Branch and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results and Discussion: The Gold Savings Program has been shown to have a direct, positive, and significant impact on investment interest and customer trust. However, customer trust does not significantly influence investment interest, thereby automatically ruling out its mediating effect. This confirms that the program’s technical practicality and economic appeal directly trigger investment decisions without requiring a prior relational bond. Implications: Sharia financial institutions are recommended to prioritize simplifying access and digital services in order to promote financial inclusion. Researchers are further advised to expand the demographic scope and explore variables related to financial literacy or risk perception. Originality: This study offers a novel perspective by revealing the anomalies and limitations of applying Trust-Commitment Theory to the demographics of developing societies through the adaptation of the Stimulus-Organism-Response framework.